NEED TO CHANGE MUSIC COURSES ACCORDING TO THE PRESENT TIME: वर्तमान समयानुसार संगीत पाठ्यक्रमो में बदलाव की आवशयकता - Marathe, Swapna (International Journal of Research -GRANTHAALAYAH, 2015)
Age change is the related rule of creation, under which social, cultural, political environment also changes. Therefore, it is not surprising to have a change in the method of classical music education. Indian culture is one of those cultures of the world which gave new direction and creativity to the entire world. This is the place where our culture lovers have sacrificed their entire lives to keep it safe. Music is an artistic achievement of human society. It is an iconic symbol of rhythmic cultural traditions and is a masterpiece of spirit. Music is the only medium to give abstract form to tangible form and music is present everywhere in the people according to the interest of music due to its idol form. युग परिवर्तन सृष्टि का सम्बन्धित नियम है, जिसक¢ अन्तर्गत सामाजिक, सांस्कृतिक, राजनीतिक वातावरण भी बदलते रहते हैं। अतः युगानुकूल संगीत षिक्षा की पद्धति में भी परिवर्तन ह¨ना आष्चर्यजनक घटना नहीं है। भारतीय संस्कृति विष्व की उन संस्कृतिय¨ं में से एक है जिसने सम्पूर्ण विष्व क¨ नई दिषा एवं सृजनात्मकता दी। ये व¨ धर¨हर है जिसक¨ सुरक्षित रखने क¢ लिये हमारे संस्कृति प्रेमिय¨ं ने अपने सम्पूर्ण जीवन की आहूति दी। संगीत मानव समाज की एक कलात्मक उपलब्धि है। यह लयकारी सांस्कृतिक परम्पराअ¨ं का एक मूर्तिमान प्रतीक है अ©र भावना की उत्कृष्ट कृति है। अमूर्त भावनाअ¨ं क¨ मूर्त रूप देने का माध्यम ही संगीत है एवं मूर्ति रूप ह¨ने क¢ कारण संगीत ल¨क रुचि क¢ अनुरूप जन-जन में सर्वत्र विद्यमान है।